Quantitative analysis of internal wave detection variability in the Northern Gulf of California using Synthetic Aperture Radar - Gámez, Diego; Shirasago, Bernardo; Pérez, Edgar (Tecnología y ciencias del agua, 2018)
Gámez, D., Shirasago, D., & Pérez, E. (January-February, 2018). Quantitative analysis of internal wave detection variability in the Northern Gulf of California using Synthetic Aperture Radar. Water Technology and Sciences (in Spanish), 9(1), 125-133, DOI: 10.24850/j-tyca-2018-01-09.Â Â  Â The islands Tiburon and Angel de la Guarda are located toward the northern part of the Gulf of California (NGC), these are commonly referred to as the Midriff Island zone. These islands are surrounded by channels and sills, which in interaction with tides propitiate the conditions for strong water column mixing, and together with the topography and stratification produce internal waves (IW). The Synthetic Aperture Radar (SAR) has demonstrated its capacity to detect IW at important oceanic areas. In this study, the seasonal and inter-annual variability of IW was determined for the first time using "quick-lookâ€ SAR images (SI) at NGC during the period of 2000-2006. Â